Transport conditions of mountain-surging glaciers as recorded in the micromorphology of quartz grains (Medvezhiy Glacier, West Pamir) - Muzińska, Agnieszka (Geologos, 2015)
In order to reproduce the conditions under which sediments were transported in surging glaciers, samples were taken from the margin and foreland of the surge Medvezhiy Glacier situated in West Pamir (Tajikistan). They were subjected to an analysis of rounding and frosting of quartz sand grains (0.8-1.0 mm) and of grain surface micromorphology under scanning electron microscope (SEM). Results obtained showed intense chemical weathering occurred in the majority of quartz grain surfaces, marked in the form of etching and precipitation. Frequencies of microstructures of glacial origin were low; individual microstructures were visible on single grains. A predominance of the crushing process over abrasion in transformation of quartz grains was noted. The commonest microstructures connected with a surge-glacier environment were large and small conchoidal fractures. However, grains with primary features not connected with a glacial environment were equally common. The majority of the grains examined showed features of multiple cycles of mechanical and chemical weathering forming a microtexture under various conditions (overprinting). Common features of grains from surging glaciers are also breakage blocks of >10μm, which depend of the phase of separation of the grain from the rock or on thermal changes in the glacier’s foreland.